ADOLESCENTS SERVING TIME WITHOUT RESTRICTION OF FREEDOM, DUE THE EDUCATIONAL CHARACTER OS THE MEASURE OF COMMUNITY SERVICE AND DEVELOPMENT OF VALUES: A BIBLIOGRAFIC REVIEW - Ferreira, Vanessa Gimenez [UNESP]; Nogueira da Cruz, Luciana Aparecida [UNESP] (Fundacao Univ Tocantins, 2022)
This study aimed to analyze the publication of scientific from the years 2010 to 2020, with the theme of adolescents serving time without restriction of freedom, due to the educational character of the measure (in Brazil it's called medida socioeducativa - MSE) of Community Service (in Brazil it's called prestacao de servicos a comunidade - PSC). A bibliographic review was carried out in the databases. Seven articles and three master's dissertations were used to compose this bibliographic review and only one of the articles refers about adolescents serving time without restriction of freedom, and among them the PSC. No specific articles on PSC were found; two marter's dissertations address the adolescent's perception of PSC, highlighting the potential for the development of values and the guarantee of human rights, but points out the weaknesses and the need to review it. It is noticed that there are still few studies and researches in cases that adolescents are sentenced to serve time when sentenced to sentences without restriction of freedom, mainly on PSC. Therefore, this bibliografic review proved to be fundamental in the sense of pointing out research topics that can contribute to the formation and educational processes of adolescents.
Keywords: Educational Measures; Adolescents; Education in Values